If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2/3(4x-7)=-3
We simplify the equation to the form, which is simple to understand
2/3(4x-7)=-3
Simplifying:
+ 0.666666666667*(4x-7)=-3
Reorder the terms in parentheses
+(+2.66666666667x-4.66666666667)=-3
Remove unnecessary parentheses
+2.66666666667x-4.66666666667=-3
We move all terms containing x to the left and all other terms to the right.
+2.66666666667x=-3+4.66666666667
We simplify left and right side of the equation.
+2.66666666667x=+1.66666666667
We divide both sides of the equation by 2.66666666667 to get x.
x=0.625000000001
| 3k+2k=6+3k | | 2x-3-4x+5=10 | | 8x+33=3-2x | | 9-3c=36 | | (5/-9)(-2/7)(-3) | | 2x+2=4x-11 | | 60+c=-10 | | 6(2x+3)-3x=63 | | 7y*4.6= | | 20-5c=50 | | 3/4m=-2/3 | | 5/-9x-2/7x-3 | | -3x+7+2x=37 | | 2/3m=3/4 | | (x^2-4)(x^2-4)=-5 | | 3x+7+2x=37 | | 2x+3+2=-1 | | 2x=103+x | | -2(4x-5)=38 | | 10=25+.5x | | 11=5(n-9) | | 6(9x+18)=60 | | 3/4m=3/7 | | 6(2y+5)=78 | | x/3-19=5 | | -4+5x=87 | | 4p-3=2p+5 | | 5(18+x)+10(4x)+25x=1420 | | 75-5n=100 | | 9x-4x+5=x-5+10 | | f(2)=-3x+9 | | 4(2-4r)=72 |